Impact of newly diagnosed extramedullary myeloma on outcome after first autograft followed by maintenance: A CMWP-EBMT study - Gagelmann Nico; Eikema Dirk-Jan; Koster Linda; Netelenbos Tanja; McDonald Andrew; Stoppa Anne-Marie; Fenk Roland; Anagnostopoulos Achilles; van Gorkom Gwendolyn; Deconinck Eric; Bulabois Claude-Eric; Delforge Michel; et al. (John Wiley and Sons Inc, 2025)
Background: No adequate data exist on the impact of multiple myeloma (MM) with extramedullary disease (EMD) after autograft and maintenance therapy.
Methods: We identified 808 patients with newly diagnosed MM who received first autograft, of whom 107 had EMD (83 paraskeletal and 24 organ involvement), and who had been reported to the EBMT registry December 2018. Distribution according to type of involvement was similar between the treatment groups (p = .69). For EMD, 46 (40%) received thalidomide, 59 (51%) lenalidomide, and 11 (10%) bortezomib.
Results: The median follow-up from maintenance start was 44 months. Three-year progression-free survival (PFS) was 52% (48%–57%) for no EMD, 56% (44%–69%) for paraskeletal involvement, and 45% (22%–68%) for organ involvement (p = .146). Early PFS (within first year) appeared to be significantly worse for organ involvement (hazard ratio, 3.40), while no significant influence was found after first year from maintenance start. Three-year overall survival (OS) was 81% (77%–84%), 88% (80%–96%), and 68% (47%–89%; p = .064), respectively. With thalidomide as reference, lenalidomide was significantly associated with better PFS and OS, whereas bortezomib appeared to improve outcome specifically in EMD.
Conclusion: Lenalidomide maintenance is standard of care for MM without EMD, whereas extramedullary organ involvement remains a significant risk factor for worse outcome, especially for early events after maintenance start.